The child's right to participate in family law proceedings : represented, heard or silenced? / Charlotte Mol. - Mol, Charlotte (European family law series ;, 2023)
In family law proceedings, such as divorce, children are afforded the right to express their views and these must be considered seriously during the deliberation by the decision-maker. This book examines the international and European human rights frameworks through the lens of the child's right to participate.